Authenticity" About Ferdowsi Neighborhoods Of Tehran with Historical Textures with the Phenomenological Approach - Samaneh Dousti; Zohreh Davoudpour; Leila Zare (تحقیقات کاربردی علوم جغرافیایی)
Urban neighborhoods are one of the vital elements of each city and the culture of urban residents is concealed in the texture and sinew of that .The advent of new technologies in urban life and percipitance of designers for construction of buildings led to reduce of fixation sense about their living environment and decrease social interaction. once the historical districts are regarded as symbols of security, comfort and authenticity of the residents, due to inefficiency and interruption of their structures, suffer instability and displacement of their residents.According to this, instability and displacement of inhabitants to districts of historical value are known as the main problem in these neighborhoods. The purpose of this study is to identify the effective factors of authenticity in historical textures of “Ferdowsi” neighborhood located in distrct 12 of Tehran by phenomenological approach.method. For this purpose, eight persons of  this neighborhood were selected by purposive sampling method were collected through questionnairs and profound individual interviews.After recording the interviews, they were implemented in Maxqda qualitative data analysis softwarethe data and analyzed by seven-based Colaizzi methods.Authenticity as one of the individual characteristics will have an effective factor in educating people to live as citizens in the external society and will have a controlling role on human behavior and performance in society. Therefore, preserving and protecting valuable historical monuments, buildings and places. In a neighborhood that is subject to the behavioral and functional characteristics of human beings, in addition to the permanence and sensory richness of the permanence and sensory richness of the space, it will be necessary to transfer originality from one generation to another.